THE ROMANCE FORMULA IN LISA KLEYPAS RAINSHADOW ROAD - Nurul Safitri; Ratna Sari Dewi (PHILOLOGY Journal of English Language and Literature, 2021)
This thesis analyzes the novel entitled Rainshadow Road by Lisa Kleypas. The purpose of this study is to describe the romance formulas that exist in popular literary novels. In analyzing this thesis, the process of searching for data and information uses library and journal methods from the internet. The theory that guides the work of this thesis is the theory of popular romance literature by John G. Cawelti. The results of the analysis show that the novel contains elements of the characters and the plot of the romance is built into a romance formula.